Transplantation of human embryonic stem cells onto a partially wounded human cornea in vitro. (26th January 2012) - Hanson, Charles; Hardarson, Thorir; Ellerström, Catharina; Nordberg, Markus; Caisander, Gunilla; Rao, Mahendra; Hyllner, Johan; Stenevi, Ulf
Abstract. Purpose: The aim of this study was to investigate whether cells originating from human embryonic stem cells (hESCs) could be successfully transplanted onto a partially wounded human cornea. A second aim was to study the ability of the transplanted cells to differentiate into corneal epithelial‐like cells. Methods: Spontaneously, differentiated hESCs were transplanted onto a human corneal button (without limbus) with the epithelial layer partially removed. The cells were cultured on Bowman's membrane for up to 9 days, and the culture dynamics documented in a time‐lapse system. As the transplanted cells originated from a genetically engineered hESC line, they all expressed green fluorescent protein, which facilitated their identification during the culture experiments, tissue preparation and analysis. To detect any differentiation into human corneal epithelial‐like cells, we analysed the transplanted cells by immunohistochemistry using antibodies specific for CK3, CK15 and PAX6. Results: The transplanted cells established and expanded on Bowman's membrane, forming a 1–4 cell layer surrounded by host corneal epithelial cells. Expression of the corneal marker PAX6 appeared 3 days after transplantation, and after 6 days, the cells were expressing both PAX6 and CK3. Conclusion: This shows that it is possible to transplant cells originating from hESCs onto Bowman's membrane with the epithelial layer partially removed and to get these cells to establish, grow and differentiate into corneal epithelial‐like cells in vitro.